Mitigasi Daerah Rawan Bencana Longsor Di Kota Batu Dengan Menggunakan Metode Analisis SIG - Noviari, Salsabila; Salfira, Ginanda; Raudhah, Amna Fithri; Haerudin, Nandi; Mulyasari, Rahmi (Journal of Applied Geoscience and Engineering, 2023)
Landslide is one of the natural damages caused by mass movement in a natural landscape. The occurrence of landslides causes damage that provides direct and indirect risk effects. Efforts made to reduce the effects of risk can be done by mitigation planning. Batu City is one of the cities located at the foot of Mount Panderman, located at 700-1100 meters DPL. Research was conducted to determine landslide prone areas based on GIS which can then be carried out a sustainable mitigation process. In this area, research was conducted by utilizing GIS in the form of mapping landslide prone areas. Batu city has a predominantly very steep slope that causes high landslide prone areas. Therefore, GIS method can be utilized in mapping landslide vulnerability in Batu city as a map editor and data processor of spatial area which includes rainfall data, soil type data, slope data, and land cover type data.